Globalisation and Inequality: Where do we stand? - Chusseau, Nathalie; Hellier, Joël (Journal of Income Distribution®, 2014)
Both developed and developing countries have experienced a huge globalization of their economies and an increase in within-country income inequality. We survey the literature on the globalization-inequality relationship. The extension of the North-South Heckscher-Ohlin-Samuelson (HOS) approach by relaxing certain simplifying assumptions makes it possible to generate most of the observed facts. Production segmentation and offshoring increase inequality in developed and developing countries. Firm heterogeneity generates intra-skill group inequality. Globalization causes changes in technologies and in institutions that can foster inequality. Most of these mechanisms combine globalization with technological or/and institutional changes, which reconcile the three major explanations for the rise in inequality.